2018
DOI: 10.1177/1545968317753681
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Width Does Not Influence the Gains Achieved With Neuromuscular Electrical Stimulation in People With Multiple Sclerosis: Double-Blind, Randomized Trial

Abstract: There was no influence of stimulus-pulse duration on the primary outcomes (gait speed and walking endurance). The 6-week NMES intervention applied to the lower leg muscles of persons with mild to moderate levels of disability can improve their walking performance and provide some symptom relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Despite both groups leading to improve functionality with lower pain, EMS/CG resulted in better improvements compared to the CG, assuming the more beneficial effect of EMS training on PFP women. These results agree with previous studies and expand our knowledge about the effects of EMS training on PFP individuals, showing that EMS could provoke better results compared to the conventional alone [20] This finding is also consistent with previous studies, showing positive effects of EMS training both in healthy [36], non-healthy individuals [37] and in post-operation rehabilitation [27]. Besides the benefits in muscle strength, the use of EMS training in healthy older persons led to improved speed gait and walking endurance after the first six weeks of intervention, while the dynamic balance improved after the seventh week [36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite both groups leading to improve functionality with lower pain, EMS/CG resulted in better improvements compared to the CG, assuming the more beneficial effect of EMS training on PFP women. These results agree with previous studies and expand our knowledge about the effects of EMS training on PFP individuals, showing that EMS could provoke better results compared to the conventional alone [20] This finding is also consistent with previous studies, showing positive effects of EMS training both in healthy [36], non-healthy individuals [37] and in post-operation rehabilitation [27]. Besides the benefits in muscle strength, the use of EMS training in healthy older persons led to improved speed gait and walking endurance after the first six weeks of intervention, while the dynamic balance improved after the seventh week [36].…”
Section: Discussionsupporting
confidence: 93%
“…Besides the benefits in muscle strength, the use of EMS training in healthy older persons led to improved speed gait and walking endurance after the first six weeks of intervention, while the dynamic balance improved after the seventh week [36]. Similarly, it was previously found that people with multiple sclerosis increase gait velocity, and walking endurance with the use of EMS in their rehabilitation process [37], suggesting the global influence of EMS [29]. It has been reported a possible global effect of the EMS training applied to the quadriceps muscle, leading to increases in hamstrings strength as well [27].…”
Section: Discussionmentioning
confidence: 60%
“…The authors explain the discrepancy by a reduced voluntary muscle activation of agonists muscles, which cause limitations in muscle activation as reflected by a lower amplitude in PwMS 55 . Reduced firing rates in PwMS were also associated with reduced walking speed and distance 72 . Rice et al offer some explanation into the underlying mechanisms in a small study examining muscle weakness including 4 PwMS and 16 HC.…”
Section: Discussionmentioning
confidence: 99%
“…Both wide pulses (1 ms [10]) and narrow pulses (200 μs [12]) increased motor unit outputs in the targeted muscle. In a clinical setting where patients with multiple sclerosis participated in TENS and training sessions to improve motor function, Almukass et al [42] found similar clinical outcomes with stimulators delivering narrow (200 μs) and wide (1 ms) pulses. When considering the frequency, stimulations at 100 Hz were the most effective to increase motor unit output [10, 11] or increase corticospinal excitability [43].…”
Section: Discussionmentioning
confidence: 99%